Pilgrim’s Motivations: A Theoretical Approach to Pilgrimage as a Peacebuilding Tool - Sílvia Aulet Serrallonga (International Journal of Religious Tourism and Pilgrimage)
This paper will explore the relationship between pilgrimage and peacebuilding. Studies on peace refer to three dimensions: peace from a personal dimension and spiritual sphere; peace from a social dimension and; peace from an environmental dimension (Sánchez Sánchez & Fernández Herreira, 1996). The connection between pilgrimage and peacebuilding starts with the individual quest of pilgrims; however, can be explored in the other two dimensions. The experience of pilgrimage and the pilgrims’ quest for inner peace can enhance a respectful attitude towards people and places. Through interviews and observation on two pilgrimage routes in Spain (the Camino de Santiago and Camino Ignaciano) the links between pilgrimage and peacebuilding are explored. Results show a strong connection between pilgrimage and inner peace and pilgrimage and social peace. This connection is not so strong in the case of the environmental dimension of peace.